2014
DOI: 10.1073/pnas.1408835111
|View full text |Cite
|
Sign up to set email alerts
|

Energy landscape of self-assembled superlattices of PbSe nanocrystals

Abstract: Self-assembly of nanocrystals (NCs) into superlattices is an intriguing multiscale phenomenon that may lead to materials with novel collective properties, in addition to the unique properties of individual NCs compared with their bulk counterparts. By using different dispersion solvents, we synthesized three types of PbSe NC superlattices-body-centered cubic (bcc), body-centered tetragonal (bct), and face-centered cubic (fcc)-as confirmed by synchrotron small-angle X-ray scattering. Solution calorimetric measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…3(d). 3. bco-like crystal: This construction uses a Bain transformation 70,71 that views the fcc crystal of hard spheres as a special body-centered-orthorhombic (bco) crystal [ Fig. 4(a)].…”
Section: Dense Packing Constructionsmentioning
confidence: 99%
“…3(d). 3. bco-like crystal: This construction uses a Bain transformation 70,71 that views the fcc crystal of hard spheres as a special body-centered-orthorhombic (bco) crystal [ Fig. 4(a)].…”
Section: Dense Packing Constructionsmentioning
confidence: 99%
“…1,2 Colloidal NCs stabilized by organic surfactants have been shown to pose excellent building blocks for the design of synthetic MCs with tailored structural properties which are conveniently obtained by self-assembly of NCs from solution on a solid or liquid substrate by exploiting ligand-ligand 3 interactions. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Typically, the utilized ligands consist of wide-gap, bulky hydrocarbons which render the MCs insulating. [26][27][28][29][30][31][32][33] MCs obtained in this way exhibit average grain sizes of ~150 µm 2 , which enables a detailed characterization by electron and/or X-ray microscopy.…”
mentioning
confidence: 99%
“…The latter is mostly observed around larger blebs or rods and is also associated with an increase in the offset in the orientation between clausthalite and the host. Self-assembly of nanocrystals into superlattices has been documented experimentally in PbSe, with three types of atom packing, one of which is tetragonal [51]. However, the superlattices given by Quan et al [51] are smaller than those observed here in the tetragonal chalcopyrite matrix.…”
Section: Formation Of Clausthalite In Cu-(fe)-sulphidesmentioning
confidence: 44%
“…Self-assembly of nanocrystals into superlattices has been documented experimentally in PbSe, with three types of atom packing, one of which is tetragonal [51]. However, the superlattices given by Quan et al [51] are smaller than those observed here in the tetragonal chalcopyrite matrix. None of the FFTs or SAEDs obtained from the mottled areas show the simple lattice of clausthalite (as, for example in the CcI study case) but instead show satellite reflections on SAEDs, representative of chalcopyrite on different zone axes.…”
Section: Formation Of Clausthalite In Cu-(fe)-sulphidesmentioning
confidence: 44%